Keterlibatan Pihak Ketiga Dalam Perjanjian Pinjaman Online - Leluly, Hervy Welem; Pesulima, Theresia Louize; Balik, Agustina (PATTIMURA Law Study Review, 2025)
Financial Services Authority Regulation Number 10/POJK.05/2022 concerning Information Technology-Based Joint Funding Services, in Article 44 paragraph (1) letter c states that: "Organizers are obliged to guarantee that the acquisition, use, utilization and disclosure of personal data, transaction data and financial data obtained by the organizer based on the consent of the owner of the personal data, transaction data and financial data, unless specified by statutory provisions. However, in online loan transactions it is often found that a third party is involved as an emergency contact unilaterally, which is done by using personal data in the form of name and telephone number without prior approval and usually the third party is considered a guarantor for the loan made. The type of research used in this writing is normative juridical legal research using a statutory approach and a conceptual approach. The legal materials used are primary, secondary and tertiary legal materials. Analysis of legal materials is carried out qualitatively, namely the materials that have been collected are then analyzed to answer the problems that occur. The research results show that a third party cannot be used as a guarantor for the debtor's debt if there is no guarantee agreement between the third party and the debtor. The third party is only limited to reminding the debtor of the bill. And creditors have no right to collect and intimidate third parties. The protection that can be provided for misuse of third party personal data added unilaterally is through a lawsuit against the law under Article 1365 of the Civil Code and the creditor can report it to the Financial Services Authority (OJK).